Hospital certificate-of-need controls : Impact on investment, costs, and use - Salkever, David S.; Bice, Thomas W. (Washington : American Enterprise Institute, 1979)
The present study is fully consistent with the general locus of NCHSR interests, but it is more than that. It touches upon all three of these research concerns-: hospital responses to regulation, variations in use and costs, and the role of increasing service intensity. The study poses the basic question of whether certificate-of-need legislation has achieved its intended effects.
Includes bibliographical footnotes.
ne 24/05/2018
Loan
Keywords: Health facilities; Hospitals; Hospital utilization